Software to Visualize Proteins and Perform Structural Alignments. Issue 11 (23rd November 2021) - Barber, Robert D.
Abstract: Availability of protein structural data is accelerating at an astounding rate, facilitating in silico biochemical and biophysical analyses that require visualization methods. In particular, increased accessibility of representatives within respective protein families is empowering investigators to perform structural model comparisons that provide both functional and evolutionary insights at much more refined levels than previously possible. Numerous software platforms, including several free and open source versions, are available for users to interrogate protein structural models. In this article, three structural alignment protocols are described using freely available software to investigate aspects of protein structure evolution at quaternary, tertiary, and domain levels, respectively. Mapping distinct subunit interfaces and active site positioning within the PfpI/DJ‐1 protein superfamily reveals quaternary structure that can have a prominent role in determination of distinct enzyme activities. In contrast, cytochrome c proteins are under strong evolutionary constraints due to their critical role in energy generation, and as a result, structural conservation is observed. However, substitutions within these conserved folds occur in distinct species, presumably to influence interactions with protein complexes involved in electron transport. Lastly, evolution of distinct allosteric mechanisms within winged helix‐turn‐helix transcriptional regulators, as well as protein dynamics, are revealed through visualization of metal‐ and redox‐responsive DNA‐binding proteins. The software platforms used in these protocols are Swiss‐PDBViewer and PyMOL. Swiss‐PDBViewer is an easy to implement, end‐user software that is excellent for entry into protein visualization methods. PyMOL is also easy to implement, but offers greater depth for advanced investigations and visualizations, as well as the ability to capture protein structure conformational changes. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Exploring quaternary structure evolution with Swiss‐PDBViewer Alternate Protocol : Exploring tertiary structure evolution with Swiss‐PDBViewer Basic Protocol 2 : Visualizing allostery using PyMOL